Nickel titanium T-loop wire dimensions for en masse retraction - Almeida, Layene [UNESP]; Ribeiro, Alexandre; Martins, Renato Parsekian [UNESP]; Viecilli, Rodrigo; Martins, Lidia Parsekian [UNESP] (E H Angle Education Research Foundation, Inc, 2016)
Objective: To compare the force system produced by nickel-titanium T-loop springs made with wires of different dimensions. Material and Methods: Thirty compound T-loop springs were divided into three groups according to the dimensions of the nickel-titanium wire used for its design: 0.016 x 0.022, 0.017 x 0.025, and 0.018 x 0.025. The loops were tested on the Orthodontic Force Tester machine at an interbracket distance of 23 mm and activated 9 mm. The force in the y-axis and the moment in the x-axis were registered while the calculated moment to force ratio was recorded at each.5 mm of deactivation. The data were analyzed by three analyses of variance of repeated measures to detect differences and interactions between deactivation and wire size on force, moment, and moment-force ratios (M/F). Results: All groups had significantly different forces (P <.001). The 0.016 x 0.022 wire produced 1.78N of force while the 0.017 x 0.025 and the 0.018 x 0.025 produced 2.81 N and 3.25 N, respectively. The 0.016 x 0.022 wire produced lower moments (11.6 Nmm) than the 0.017 x 0.025 and 0.018 x 0.025 wires, which produced similar moments (13.9 Nmm and 14.4Nmm, respectively). The M/F produced was different for all groups; 0.016 x 0.022 T-loops produced 6.7 mm while the 0.017 x 0.025 and 0.018 x 0.025 T-loops produced 5.0 mm and 4.5 mm, respectively. An interaction was detected for all variables between deactivation and groups. Conclusion: The larger wires tested produced higher forces with slight increase on the moments, but the M/F produced by the 0.016 x 0.022 wire was the highest found.
Keywords: T-loop; NiTi; Orthodontics